Fetal Growth Restriction in Patients with Adenomyosis. Incidence and Mechanism - Elena-Adriana GHELMENE; Natasia SERBAN; Manuela Cristina RUSSU (Modern Medicine)
Reports on adenomyosis in pregnancy are few and include a small number of patients. Currently, ultrasound is the first-line imaging diagnostic tool, with a sensitivity of about 84%. Controversies exist regarding the relation of adenomyosis with infertility and pregnancy complications. We analyzed the intrauterine growth restriction (IUGR) cases for a period of one year aiming to determine if adenomyosis impacts negatively the pregnancy outcome. The preterm birth rate in our study population was 20%. From the preterm birth subgroup, the greatest percentage was attributed to late prematurity. The incidence of adenomyosis in this group of pregnancies complicated with IUGR was about 9%. According to our results, there is a higher incidence of preterm birth in cases complicated with fetal growth restriction, as reported by other much larger studies. At this point, there is no established associated risk or method to prevent unfavorable outcomes related to the impact of adenomyosis on pregnancy.